Socioeconomic spatial analysis through fuzzy system as a tool for territorial planning applied to watersheds - Arantes, Leticia Tondato [UNESP]; dos Santos, Arthur Pereira [UNESP]; Silva, Camille Vasconcelos [UNESP]; Nery, Liliane Moreira [UNESP]; Toledo, Mayra Vannessa Lizcano [UNESP]; Simonetti, Vanessa Cezar; da Cunha e Silva, Darllan Collins [UNESP]; Lourenço, Roberto Wagner [UNESP] (Taylor & Francis, 2024)
The watersheds are fundamental in the management of social policies, allowing for the measurement of physical and socioeconomic characteristics through indicators such as the HDI and SII. This study aims to develop the Socioeconomic Analysis Indicator (SAI) for the sub-basins of the Sorocabuçu River (SRB), using a fuzzy system and geoprocessing tools for zoning information by sub-basins. The HDI of the SRB resulted in high values, with income showing the lowest indices, followed by education and longevity. The SII showed low values, with income and literacy significantly contributing to socioeconomic vulnerability. The SAI results indicated reasonable socioeconomic conditions, with lower values in the sub-basins farther from urban and urbanized areas. This study provides data for the establishment of public policies aimed at reducing social and economic inequalities, prioritizing the most vulnerable sub-basins. The data obtained serve as an effective tool to support public management, promoting decisions that improve the quality of life of the local population through the integration of socioeconomic variables for a more holistic and sustainable approach to watershed management.
Keywords: geoprocessing; indicators; Management; planning; watersheds